A Direct Near-Field Observation of Conversion Between Waveguide Modes and Leaky Modes in Periodic Metal Structures - Chia Ho Wu; Zhenyu Qian; Wei Wang; Jianqi Shen; Xianqing Lin; Li-Yi Zheng; Fang He; Xiaolong Wang; Zhuoyuan Wang; Song Tsuen Peng; Guobing Zhou; Linfang Shen; et al. (IEEE Access, 2023)
In order to directly observe the conversion between guided-wave modes and leaky-wave modes in a periodic structure, quadrilateral periodic metal diaphragms arranged in two ways on metal surfaces were analyzed. In the first scheme, each unit cell in the periodic structure contains a metal diaphragm, of which the dispersion characteristics of periodic structures were analyzed by the finite element method. The results of the numerical simulation show that by adjusting lattice constants of periodic structures and geometrical parameters of metal diaphragms, the transmission bandwidth of the present 1-D periodic metal diaphragm structures could be limited to X-band, where the transmission characteristics are easy to be measured. In the second scheme, a pair of mirror-symmetric and staggered quadrilateral metal diaphragms is introduced into a unit cell. It can be found in the theoretical calculation that a new dispersion curve, which passes through the light line in a high frequency range, can be exhibited. The propagation constants of dispersion curves become complex numbers and provide highly directional electromagnetic radiation that scans as the frequency changes. After the relative positions of the two metal diaphragms were properly adjusted, the frequency range of the forbidden band gap between two dispersion curves can be minimized, so as to increase the transmission bandwidth of the 1-D periodic metal structures. The experimentally measured results show that the dispersion curves of the two periodic structures were highly consistent with the theoretical results. The narrowing of the band gap could be verified by measuring the $S$ -parameters. The near-field measurement of the periodic metal structures can demonstrate the conversion between the guided-wave modes and the leaky-wave modes, and the far-field measurement can show the frequency dependence of beam elevation. We expect that these artificial material structures could be widely used for designing new microwave and terahertz band devices.